Pelatihan Bermain Kata dalam Meningkatkan Kecerdasan Linguistic pada Siswa Kelas III SDN Putat Kidul 02 Malang - Arief Rahman Hakim (Universitas Muhammadiyah Ponorogo, 2019)
Playing is one way to develop students' linguistic intelligence. Well-designed play will make students unconsciously learn. Students can be active, volunteer, without coercion. This devotion program is in the form of word play training on third grade students of SDN Putat Kidul 02 Gondanglegi Kabupaten Malang